WORK PLACES VIOLENCE TOWARDS CLINICAL NURSES IN TEACHING HOSPITALS, A REVIEW (The Research of Medical Science Review, 2025)
Workplace violence (WPV), such as what nurses’ experience against them when specifically exclaimed, is a serious problem in the health environment. The effects of workplace violence present on nurses include deterioration of physical and mental health and substandard patient care. In this paper, WPV has been defined to include the three primary types of abuse experienced by nurses, which are verbal, physical, and psychological abuse. Reviewing different international studies, including studies from Hong Kong, the U.S., Saudi Arabia, and Pakistan, a similar set of factors emerged as follow: heavy workloads, understaffing, and patient aggression. Verbal abuse is very usual, especially in emergency departments, while psychological effects mostly derived from anxiety, burnout, and job dissatisfaction are also common. WPV results in high turnover rates among the nursing workforce. This study advocates the need for effective management strategies in the direction of zero tolerance policies, improved reportings, as well as workplace safety measures. The paper also identifies the absence of policies in Pakistan on WPV and calls for systemic reforms to prevent this from happening to nurses and improve their working conditions.